A pilot trial of repetitive transcranial magnetic stimulation of the dorsomedial prefrontal cortex in anorexia nervosa: resting fMRI correlates of response - Woodside, D. Blake; Dunlop, Katharine; Sathi, Charlene; Lam, Eileen; McDonald, Brigitte; Downar, Jonathan (Journal of eating disorders, 2021)
Background Patients with anorexia nervosa (AN) face severe and chronic illness with high mortality rates, despite our best currently available conventional treatments. Repetitive transcranial magnetic stimulation (rTMS) has shown increasing efficacy in treatment-refractory cases across a variety of psychiatric disorders comorbid with AN, including major depression, Obsessive Compulsive Disorder (OCD), and Post traumatic Stress Disorder (PTSD). However, to date few studies have examined the effects of a course of rTMS on AN pathology itself. Methods Nineteen patients with AN underwent a 20–30 session open-label course of dorsomedial prefrontal rTMS for comorbid Major Depressive Disorder (MDD) ± PTSD. Resting-state functional MRI was acquired at baseline in 16/19 patients. Results Following treatment, significant improvements were seen in core AN pathology on the EDE global scale, and to a lesser extent on the shape and weight concerns subscales. Significant improvements in comorbid anxiety, and to a lesser extent depression, also ensued. The greatest improvements were seen in patients with lower baseline functional connectivity from the dorsomedial prefrontal cortex (DMPFC) target to regions in the right frontal pole and left angular gyrus. Conclusions Despite the limited size of this preliminary, open-label study, the results suggest that rTMS is safe in AN, and may be useful in addressing some core domains of AN pathology. Other targets may also be worth studying in this population, in future sham-controlled trials with larger sample sizes. Trial registration Trial registration ClinicalTrials.gov NCT04409704 . Registered May 282,020. Retrospectively registered. Plain English summary Anorexia nervosa is a serious illness that is difficult to treat. New treatments are urgently needed. This paper describes a preliminary study of a potential new treatment for Anorexia Nervosa, transcranial magnetic stimulation. In this treatment a magnetic field is generated and applied from outside the skull to affect specific areas of the brain thought to be involved in Anorexia nervosa. The results of this preliminary trial, conducted with 19 subjects over 6 weeks, showed some improvements in the way people with Anorexia nervosa think about weight, shape and their eating. The benefits were associated with areas of the brain involved in decision making and in regulating emotions. These changes did not appear to be related to improvements in other conditions, such as depression.